Relé de proteção virtual: simulador web para relés de proteção - Hoffmann, Bruna Ventura (2023)
The protection relays are the main devices of a protection system, and it is essential that before their actual deployment in the electrical system, they are tested. It is important that these tests are safe and effective to evaluate how the protection equipment will operate correctly after installation. In this work, a solution, and the operation of a protection relay simulator available on the web (virtual environment) are presented, which can be accessed from anywhere using only a computer, with the aim of making protection algorithm testing more accessible. By using this protection relay simulator, it is possible to analyse, test, and change settings of a digital relay in a way similar to what is done physically in a laboratory, but with the convenience of accessing it through a web page. The web simulator is divided into three main blocks. The “Signal Processing” block is intended to adapt the current and voltage signals só that they can be used for protection function calculations. There is also the “Protection Algorithms” block for executing protection functions; in this work, the distance protection function (ANSI 21) will be presented. Finally, the “Web Interface” block is responsible for running the graphical interface. The input of current and voltage signals is done through a COMTRADE file. After the implementation of the protection relay simulator, some simulations of different types of faults on a 100 km transmission line were carried out, applying the distance functions modelled in the simulator. To demonstrate the results, comparisons were made of the performance of the MHO distance protection using different anti-aliasing filter models, A/D converter settings, and digital filters implemented. Different configurations of MHO and Quadrilateral distance functions were also demonstrated, as well as variations between the polarizations of each. The results were consistent with signal processing and power system protection theories, and it was possible to characterize and visualize the operation of MHO and Quadrilateral distance protections. The tool offered easy accessibility through its availability on a web page.